Respostas
respondido por:
6
(1/8) elevado a (2 - 3x) = 32 elevado a (4 + x)
(1/2³) elevado a (2 - 3x) = (2 elevado a 5) elevado a (4 + x)
(2 elevado a -3) elevado a (2 - 3x) = (2 elevado a 5) elevado a (4 + x)
2 elevado a (-6 + 9x) = 2 elevado a (20 + 5x)
Temos uma igualdade de potências de mesma base, portanto, os expoentes também são iguais, logo:
-6 + 9x = 20 + 5x ⇒ 9x - 5x = 20 + 6
4x = 26 ⇒ x = 26/4 = 13/2
S = {13/2}
(1/2³) elevado a (2 - 3x) = (2 elevado a 5) elevado a (4 + x)
(2 elevado a -3) elevado a (2 - 3x) = (2 elevado a 5) elevado a (4 + x)
2 elevado a (-6 + 9x) = 2 elevado a (20 + 5x)
Temos uma igualdade de potências de mesma base, portanto, os expoentes também são iguais, logo:
-6 + 9x = 20 + 5x ⇒ 9x - 5x = 20 + 6
4x = 26 ⇒ x = 26/4 = 13/2
S = {13/2}
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás